Persepsi Pelaku UMK Terhadap Penyaluran Kredit Bank Kalbar Syariah Dalam Pemulihan Masa Pandemik Covid-19 - Rio Laksamana (Jurnal Ilmiah Ekonomi Islam, 2023)
MSMES are one of the important pillars for a country's economy, especially in Indonesia. After being hit by the Covid-19 pandemic storm which had a bad impact on all elements of the government, including MSMES. The government provides support to the business world in the process of business continuity during the recovery period. Various programs include Interest Subsidy, Placement of Government Funds at Partner Commercial Banks in supporting the expansion of working capital loans to MSME loan restructuring, MSME Working Capital Loan Guarantee, Micro Business Productive Banpres, Cash Assistance for PKL and Warung, and MSME Final Income Tax incentives covered Government (DTP). The purpose of this study was to find out the perception of MSES actors on lending at Bank Kalbar Syariah in recovering from the Covid-19 pandemic. This research is a quantitative descriptive study collected by questionnaire. Respondents amounted to 194 MSEs spread throughout the city of Pontianak. This study shows that the perception of MSES players on lending at Bank Kalbar Syariah in the recovery period of the Covid-19 pandemic is still low (not yet maximized).